Synergistic Use of Remote Sensing and Modeling for Tracing Dust Storms in the Mediterranean - D. G. Kaskaoutis; A. K. Prasad; P. G. Kosmopoulos; P. R. Sinha; S. K. Kharol; P. Gupta; H. M. El-Askary; M. Kafatos (Advances in Meteorology)
This study focuses on the detection of the dust source region and monitoring of the transport of the dust plume from its primary outflow to final deposition. The application area is the Sahara desert and the eastern Mediterranean, where two dust events occurred during the period 4–6 February 2009, an unusual event for a winter period. The Aqua-MODIS and OMI observations clearly define the spatial distribution of the dust plumes, while the CALIPSO observations of total attenuated backscatter (TAB) at 532 nm, depolarization ratio (DR), and attenuated color ratio (1064/532 nm) on 5 February 2009 provide a clear view and vertical structure of the dust-laden layer. The dust source region is defined to be near the Chad-Niger-Libyan borders, using satellite observations and model (DREAM) output. This dust plume is vertically extended up to 2.5 km and is observed as a mass plume of dust from surface level to that altitude, where the vertical variation of TAB (0.002 to 0.2) and DR (0.2–0.5) implies dust-laden layer with non-spherical particles. CALIPSO profiles show that after the dust plume reached at its highest level, the dust particles start to be deposited over the Mediterranean and the initial dust plume was strongly attenuated, while features of dust were limited below about 1–1.5 km for latitudes northern of ~36° (Greek territory).